2014
DOI: 10.1179/1743294414y.0000000315
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosion of thermal sprayed Al–Zn–Si coating in simulated marine environments

Abstract: The Al-Zn-Si coating was deposited on Q235 steel by thermal spray technology. The corrosion behaviour of the coating in simulated marine environments has been investigated through neutral salt spray test (NSS) and electrochemical test. Furthermore, the microstructure and the morphologies of the coating were detected by means of scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction. The results showed that the coating exhibited a dense homogeneous lamellar microstructure without obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…The corrosion current densities of the AH32 and NiCrAlY(Ag) coatings were of the order of 10 −5 A, which was one order higher than that of the NiCrAlY coating, 4.85× 10 −6 A cm −2 . The corrosion resistance of a Ni-based spray coating with a rough surface and porous structure might deteriorate compared to that of Ni-based body materials [35], and that of aluminium is also poor in marine environments [36]. Therefore, the corrosion current of Ni-coated AH32 decreased by only one order of magnitude.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…The corrosion current densities of the AH32 and NiCrAlY(Ag) coatings were of the order of 10 −5 A, which was one order higher than that of the NiCrAlY coating, 4.85× 10 −6 A cm −2 . The corrosion resistance of a Ni-based spray coating with a rough surface and porous structure might deteriorate compared to that of Ni-based body materials [35], and that of aluminium is also poor in marine environments [36]. Therefore, the corrosion current of Ni-coated AH32 decreased by only one order of magnitude.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…Yang et al used alloy wire thermal spraying technology to prepare AlZnSi coating with lamellar structure on the surface of Q235 steel plate. In seawater corrosion experiments, it was found that the corrosion products were mainly zinc-aluminum-carbonate-sodium hydroxide hydrate, which blocked the pores and caused self-sealing behavior, hindering further corrosion [9]. In addition, Mosayebi et al prepared Ni-Mo coatings by electroplating.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal spray technologies, such as high-velocity oxygen-fuel (HVOF) spray [15,16], flame spraying [17,18] and arc spray [7,19,20] are the most common techniques to prepare Zn and Al coatings. However, due to the high process temperature of these techniques, the thermal-sprayed coatings inevitably have problems such as oxidation, phase transition, porosity and residual thermal stresses.…”
Section: Introductionmentioning
confidence: 99%